2023
DOI: 10.1186/s12872-023-03412-7
|View full text |Cite
|
Sign up to set email alerts
|

Post-COVID-19 illness and associations with sex and gender

Abstract: Background Post-COVID-19 syndromes have associated with female sex, but the pathophysiological basis is uncertain. Aim There are sex differences in myocardial inflammation identified using cardiac magnetic resonance (CMR) in post-COVID-19 patients, and in patient reported health outcomes following COVID-19 infection. Design This prospective study investigated the time-course of multiorgan injury in sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…With uCT and the other cardiovascular metrics used here, we observed that SARS-CoV-2 infection produced visual changes in uCT intensity but no quantitative changes in total lung capacity or other measures of lung function or markers of cardiovascular function in the ensuing 6 months or after a second virus inoculation administered 6 months after the first inoculation. Our observations of reduced ambulation in male but not female mice mirror post-COVID-19 outcomes in people where females experience lower rates of cardiovascular-related hospitalizations after COVID-19 ( 37 ). When subjected to a six minute walking exercise followed by pulmonary function tests, males humans also experience higher post-stress respiratory outcomes compared to females ( 38 ).…”
Section: Discussionsupporting
confidence: 52%
“…With uCT and the other cardiovascular metrics used here, we observed that SARS-CoV-2 infection produced visual changes in uCT intensity but no quantitative changes in total lung capacity or other measures of lung function or markers of cardiovascular function in the ensuing 6 months or after a second virus inoculation administered 6 months after the first inoculation. Our observations of reduced ambulation in male but not female mice mirror post-COVID-19 outcomes in people where females experience lower rates of cardiovascular-related hospitalizations after COVID-19 ( 37 ). When subjected to a six minute walking exercise followed by pulmonary function tests, males humans also experience higher post-stress respiratory outcomes compared to females ( 38 ).…”
Section: Discussionsupporting
confidence: 52%
“…From the point of view of gender differences during COVID-19 and its complications, there is a fundamental contradiction unexplained to date. In particular, men are more likely than women to experience a more severe course of COVID-19 [ 75 , 76 , 77 ], but women are more likely to experience post-COVID complications [ 16 , 22 , 25 , 62 , 64 , 77 , 78 ]. Some studies have suggested that male sex is a predictor of more severe cognitive impairment in post-COVID-19 [ 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…The increased risk of post-COVID complications in women during menopause [ 80 ] and gender differences in autoimmune response [ 75 , 81 ] are mainly discussed. A more severe acute phase of COVID-19 in men is mainly associated with a worse immune-inflammatory response [ 76 , 82 ], a lack of protective effect of sex hormones [ 81 ], and angiotensin-converting enzyme 2 (ACE2) receptor [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…For types of evaluation tools, several standardized tools were used for assessing fatigue symptoms, and some studies developed fatigue symptom checklists or questionnaires by themselves. One study validated the use of the Fatigue Severity Scale (FSS) and two single-item screening questions in two groups, and it was reported that the FSS showed a higher internal consistency and construct validity [ 70 ]. However, there is no standardized assessment tool or scale for assessing post-COVID-19 fatigue.…”
Section: Reviewmentioning
confidence: 99%